Comparison of the Structure, Physicochemical Properties, and Impact on Intestinal Flora of Processed and Unprocessed Polygonum multiflorum Starch - Guiya Yang; Ying Wang; Yuying Hu; Yue Liu; Quan Li; Shuangcheng Ma (Foods)
Polygonum multiflorum Thunb. (PM) is a starch-rich medicinal herb, but research on the changes in the structure and physical properties of the starch upon processing remains elusive. Herein, the structures and physicochemical properties, particularly the impact on intestinal flora of raw PM starch and processed Polygonum multiflorum (PMP) starch, were systematically characterized and compared. XRD and FT-IR results showed that the crystalline structure of PMP starch was disrupted, with the increase in its short-range ordering. Morphological analysis revealed that the size of PMP starch granules increased with the appearance of aggregation. Significant differences in swelling power and solubility were observed, wherein PM starch has a higher swelling power, while its solubility is lower than that of PMP starch. The PM starch also has higher thermal stability. Interestingly, the resistant starch (RS) content in PMP starch was higher, as shown by the in vitro digestibility tests, which is associated with enhanced bioactivity. Moreover, gut microbiota analysis in mice indicated that PMP starch promoted gut health by regulating specific bacterial families. Our current study has offered full insights into the changes of PM starch upon processing, laying a solid foundation for further developing PM starch-derived functional food products.